(untitled) (Cardiovascular Journal, 2013)
Background : Blood testing for biochemical markers of Myocardial injury plays an increasingly important role for the evaluation, diagnosis and triage of patients with chest pain. The guidelines for the diagnosis of Myocardial Infarction ((MI) have recently changed and prominently incorporate the results of cardiac marker testing in the clinical definition of MI. We investigated these updated biomarkers and further compare the differing biology and release kinetics of clinically relevant biomarkers. Methods: Biochemical changes that occurred in the blood of acute myocardial infarction (AMI) patients were investigated. Two hundred and fifty two patients, 180 males and 72 females were included in this study. The mean age was 49.3 ± 9.25 years. Biochemical parameters include serum triglyceride, total protein, albumin , total bilirubin and total cholesterol to albumin ratio were analyzed. Results : Biochemical parameters showed that the increased level of triglyceride and total bilirubin were associated with myocardial infarction. Triglyceride and total bilirubin levels in myocardial infarction patients were 2.3 ±1.4 mmol/ L and 12.3±3.2 ?mol/ L respectively, whereas those of healthy controls were 1.7±1.2 mmol/L for triglycerides and 9.7±3.7 ?mol/L for bilirubin. On the other hand, serum total protein and albumin concentrations were lower in MI patients compared to those of controls. Total protein level was 65.5 ±3.1 g/L in MI patients and 76.2±5.3 g/L in healthy controls. Albumin levels in both patients and controls were 40.2 ±3.2 g/L and 45.4 ± 4.5 g/L correspondingly. Conclusion : Interestingly, serum total cholesterol level was not significantly different in MI patients compared to controls. In addition, cholesterol/albumin ratio in myocardial infarction patients (0.14 ± 0.04) found to be significantly higher than in healthy controls (0.11± 0.03). Cardiovascular Journal Volume 6, No. 1, 2013, Page 43-46 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16114